A novel member of the Hemidactylus brookii complex (Squamata: Gekkonidae) from the Western Ghats of Maharashtra, India - Chaitanya, R.; Agarwal, Ishan; Lajmi, Aparna; Khandekar, Akshay (Zootaxa, 2019)
A new rupicolous gecko from the Hemidactylus brookii complex is described from the forests and plateaus of Amboli, in the Western Ghats of Maharashtra. This medium sized (average adult SVL 56.2±5.0 to at least 62 mm), nocturnal species is superficially similar to other congeners from the ‘H. brookii’ clade, but can be distinguished from them in having 17 or 18 fairly regular longitudinal rows of enlarged, conical, keeled tubercles at midbody, extending from posterior part of the head to groin; tubercles in parasagittal rows smaller, feebly keeled and more rounded; approximately six rows of tubercles on either side of parasagittal tubercle rows, highly enlarged, remarkably conical and strongly keeled; lamellae divided in a straight transverse series—seven or eight lamellae beneath fourth digit (manus and pes) and five or six beneath first digit (manus and pes). Males with nine or ten (rarely eight) femoral pores separated by four or five poreless scales; supralabials 11–13; infralabials 8–11. Molecular data based on the mitochondrial ND2 gene supports the distinctiveness of this species and helps ascertain its phylogenetic position within the ‘H. brookii’ group of the Indian Hemidactylus radiation.